PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA KOMIK KELAS VIII - Nicolas Samuel Panggabean; Hamdani Asep; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractLaw of the Republic of Indonesia Number 20 of 2003 concerning the National EducationSystem article 40 paragraph 2a states that: "Educators and education personnel areobliged to create an educational atmosphere that is meaningful, fun, creative, dynamic,and dialogical." Therefore, learning is expected to require the use of more varied deliverymedia so that the teaching and learning process creates a fun and dynamic educationalatmosphere and can be understood better. This makes teachers need to use appropriatelearning media. The media that is meant is comics media in learning mathematics withtwo-variable linear equation systems for class VIII students of SMPN 3 Sungai Ambawang.The conclusions obtained from this study are: (1) Based on the aspect of validity by onevalidator consisting of media and material experts, the assessment of material experts is3.69 and media experts is 3.84. So it can be stated that the teaching materials developedare categorized as "valid". (2) Based on the practical aspect, the average teacher responseis 3.95 and the average student response is 3.21. So that the average score of teachingmaterials is 3.58 in the "good" category. (3) Based on the aspect of effectiveness, theaverage post-test was 70.4 and the percentage of students who met the KKM was 73.91%of 23 students in the "good" category.Keywords: Comic, Development Research